Characteristics of the use of digital twins by industrial enterprises: the experience of foreign countries and Kazakhstan - Tashenova, L.V.; Babkin, A.V.; Mamrayeva, D.G.; Kulzhambekova, B.Sh. (BUKETOV BUSINESS REVIEW, 2023)
Object: digital twins, adapted to the tasks of industrial companies. Methods: content analysis for the purpose of organizing and structuring the main scientific research related to the study of the use of digital twins, their role and importance for industrial companies; the analysis method that allowed to evaluate the current state of digitalization of production processes in companies; a graphic interpretation method that allowed to visualize the obtained results. Findings: the concept of “digital twin” is considered and the aspects of its application in the sphere of industrial production are analyzed on the example of foreign companies and enterprises of Kazakhstan; the tasks of digital twins and the advantages of their implementation in production are pointed out; the stages of building digital twins were studied. Conclusions: the study showed that the use of digital twins opens up new opportunities to improve the efficiency and competitiveness of an industrial company. The results provided an opportunity to assess the annually growing interest in the technology of digital twin; based on the analyzed sources, successful examples of the implementation of digital twins in the activities of industrial enterprises of foreign countries and Kazakhstan are considered.